2013
DOI: 10.1007/s12017-013-8219-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased 5-Methylcytosine and Decreased 5-Hydroxymethylcytosine Levels are Associated with Reduced Striatal A2AR Levels in Huntington’s Disease

Abstract: Adenosine A2A receptor (A2AR) is a G-protein-coupled receptor highly expressed in basal ganglia. Its expression levels are severely reduced in Huntington's disease (HD), and several pharmacological therapies have shown its implication in this neurodegenerative disorder. The main goal of this study was to gain insight into the molecular mechanisms that regulate A2AR gene (ADORA2A) expression in HD. Based on previous data reported by our group, we measured the methylcytosine (5mC) and hydroxymethylcytosine (5hmC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(90 citation statements)
references
References 83 publications
2
86
1
1
Order By: Relevance
“…152,160,[164][165][166] Animal and cell models of HD have been fundamental in identifying the molecular mechanisms by which mHtt causes a reduction in the expression of A 2A R. Most of these models clearly show A 2A R downregulation at the protein and transcription level, but there are conflicting results when tested in the H46, YAC72, and Tg51 transgenic models. 153,164,[167][168][169][170][171] Aggregated mHtt causes changes in gene expression profiles leading to specific protein-protein interactions with several transcription factors, [172][173][174][175] while mHtt does not change gene expression relating to cytoskeleton proteins, enzymes of metabolism, mitochondrial proteins, and caspases. 164,176 Chiang et al found that mHtt expression significantly reduced the transcript levels of endogenous A 2A R in PC12 cells and striatal neurons in culture.…”
Section: Striatal Adenosine Neurotransmissionmentioning
confidence: 99%
“…152,160,[164][165][166] Animal and cell models of HD have been fundamental in identifying the molecular mechanisms by which mHtt causes a reduction in the expression of A 2A R. Most of these models clearly show A 2A R downregulation at the protein and transcription level, but there are conflicting results when tested in the H46, YAC72, and Tg51 transgenic models. 153,164,[167][168][169][170][171] Aggregated mHtt causes changes in gene expression profiles leading to specific protein-protein interactions with several transcription factors, [172][173][174][175] while mHtt does not change gene expression relating to cytoskeleton proteins, enzymes of metabolism, mitochondrial proteins, and caspases. 164,176 Chiang et al found that mHtt expression significantly reduced the transcript levels of endogenous A 2A R in PC12 cells and striatal neurons in culture.…”
Section: Striatal Adenosine Neurotransmissionmentioning
confidence: 99%
“…The genetic components responsible for their development have already been discussed above. Clinical studies aimed at treatment of Alzheimer's have affirmed a possible approach wherein in vitro or dietary administration of the components required for production of SAM like folate, homocysteine and B -group vitamins can be utilized to restore methylation levels of PSEN1, protract brain atrophy and minimize oxidative stress (Figure 3) [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94]. In addition, several HDAC inhibitors have been developed for the therapeutic strategies targeted for Alzheimer's.…”
Section: Epigenetic Therapeutics Of Neurodegenerative Disordersmentioning
confidence: 99%
“…Altered DNA methylation has recently been found in HD patients and HD transgenic mice [44][45][46]. Interestingly, Ng et al [44] showed that the promoter regions of the Ap-1, Sox2, Pax6, and Nes genes are highly methylated, and that expression levels of these genes are significantly reduced.…”
Section: Epigenetic Modifications In Hdmentioning
confidence: 99%
“…It has been shown that the adenosine A (2A) receptor (A2AR) is markedly reduced in HD and it has been implicated as a potential therapeutic target, but regulation of the A2AR gene (ADORA2A) expression is not known in HD [45]. A recent study shows that while the reduction of A2AR is correlated with increased levels of 5-methylcytosine in the 5′-UTR region of ADORA2A gene in the striatum of HD patients, A2AR down-regulation is correlated with a reduction of 5-hydroxymethylcytosine in the 5′-UTR region of the ADORA2A gene in HD transgenic mice [46].…”
Section: Epigenetic Modifications In Hdmentioning
confidence: 99%